2019
DOI: 10.1021/acs.langmuir.9b00572
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cholesterol and Bilayer Curvature on the Interaction of PPO–PEO Block Copolymers with Liposomes

Abstract: Interactions of nonionic poly(ethylene oxide)-b-poly(propylene oxide) (PEO-PPO) block copolymers, known as Pluronics or poloxamers, with cell membranes have been widely studied for a host of biomedical applications. Herein, we report how cholesterol within phosphatidylcholine (POPC) lipid bilayer liposomes and bilayer curvature affects the binding of several PPO-PEO-PPO triblocks with varying PPO content and a tPPO-PEO diblock, where t refers to a tert-butyl end group. Pulsed-field-gradient NMR was employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 80 publications
1
27
0
Order By: Relevance
“…Another possible reason is that cell membrane constituents other than the lipid molecules (e.g., cholesterol) might interfere with PEO8.4K binding to the bilayer. A recent study by our group using POPC liposomes revealed a dramatic reduction in the binding of various Poloxamers as the concentration of cholesterol was increased beyond 20 mol % relative to lipid . These two effects may operate in concert at therapeutic doses in living tissue.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Another possible reason is that cell membrane constituents other than the lipid molecules (e.g., cholesterol) might interfere with PEO8.4K binding to the bilayer. A recent study by our group using POPC liposomes revealed a dramatic reduction in the binding of various Poloxamers as the concentration of cholesterol was increased beyond 20 mol % relative to lipid . These two effects may operate in concert at therapeutic doses in living tissue.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study by our group using POPC liposomes revealed a dramatic reduction in the binding of various Poloxamers as the concentration of cholesterol was increased beyond 20 mol % relative to lipid. 57 These two effects may operate in concert at therapeutic doses in living tissue.…”
Section: ■ Discussionmentioning
confidence: 99%
“…For triblock Pluronics, N EO represents the number of repeat units of EO in one PEO block. Triblock N PO and N EO values differ slightly from those provided by the supplier, as reported in refs and .…”
Section: Methodsmentioning
confidence: 57%
“…The weight fraction of PEO ( w PEO ) was determined from the molar ratios of PPO to PEO measured by 1 H NMR spectroscopy. Details of the characterization procedures and the corresponding results were reported in our previous studies; , data relevant to the current study are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation